2004
DOI: 10.1111/j.1523-1755.2004.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of acute renal failure by serum cystatin C

Abstract: Serum cystatin C is a useful detection marker of ARF, and may detect ARF one to two days earlier than creatinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
474
7
43

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 769 publications
(546 citation statements)
references
References 48 publications
(59 reference statements)
22
474
7
43
Order By: Relevance
“…However, other studies have supported the utility of CysC as an early predictor of AKI. In a population of critically ill patients, serum cystatin C predated the identification of creatinine-based AKI by 1 to 2 days (22). In a recently published study of 100 patients undergoing CPB, the predictive capacity of plasma CysC on arrival in the ICU was excellent (AUC 0.83, 95% CI 0.68 to 0.98) for the subsequent development of AKI (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have supported the utility of CysC as an early predictor of AKI. In a population of critically ill patients, serum cystatin C predated the identification of creatinine-based AKI by 1 to 2 days (22). In a recently published study of 100 patients undergoing CPB, the predictive capacity of plasma CysC on arrival in the ICU was excellent (AUC 0.83, 95% CI 0.68 to 0.98) for the subsequent development of AKI (23).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies evaluating serum cystatin C (SCysC) as a GFR marker have shown that it performs at least as well as SCr in the population at large, and it is superior to SCr in specific patient populations (14). SCysC has also been proposed as an early biomarker of AKI in the intensive care (15,16), cardiac surgery (17), and radiocontrast administration (18) settings.…”
Section: T He Incidence Of Acute Kidney Injury (Aki) Is Increasingmentioning
confidence: 99%
“…This compound is produced at a constant rate by all nucleated cells and is filtered freely at the glomerulus and reabsorbed and catabolized but not secreted by the tubules. Cystatin C detects the development of AKI 1 to 2 d earlier than graded changes in serum creatinine as based on the ADQI/RIFLE criteria (25) and increases more rapidly than serum creatinine after administration of radiocontrast media (26). Although the accuracy of cystatin C as marker of GFR was questioned recently, particularly in inflammation (27) and patients with liver cirrhosis (28), from a pragmatic point of view, it can be supposed that if a cystatin C-based definition should be used, then physicians would be alerted 1 to 2 d earlier for the risk for AKI than by serum creatinine.…”
Section: Defining Patients At Risk For Acute Renal Injurymentioning
confidence: 99%